Connective tissue disease-associated interstitial lung disease and outcomes after hospitalization: A cohort study. (July 2019) - Ratwani, Ankush P.; Ahmad, Kareem I.; Barnett, Scott D.; Nathan, Steven D.; Brown, A. Whitney
Abstract: Background: The impact of hospitalization on patient outcomes is increasingly recognized and considered in the prognostication of many pulmonary disorders. We sought to evaluate the impact of hospitalization on survival in connective tissue disease-interstitial lung disease (CTD-ILD) patients. Methods: A chart review of patients with CTD-ILD followed at a tertiary care center was performed. Patients were stratified into two groups based on hospitalization status. Outcomes of the groups were compared using Kaplan-Meier survival analyses as well as multivariate competing risk analysis. Results: There were 137 patients identified with confirmed CTD-ILD. Patients who underwent hospitalization for any reason had a significant decrease in transplant-free survival compared to the never hospitalized cohort (3-year survival 60% vs. 94%; p = 0.0001). Hospitalization for ≥7 days was associated with worse outcomes than those hospitalized for <7 days (median survival 1.59 years vs. 7.17 years, p = 0.0012). Based on multivariate competing risk analysis, factors associated with death, with lung transplantation as a competing risk, were age (HR = 1.05 [95% 1.01–1.09]; P = 0.0443), male gender (HR = 4.94 [95% CI: 1.58–15.41]; P = 0.006), and all cause hospitalization (HR = 11.97 [95% CI: 1.36–105.49]; P = 0.0253). Conclusion: This study highlights the impact of hospitalization on subsequent outcomes in the CTD-ILD population with a significantly reduced transplant-free survival demonstrated, especially after cardiopulmonary hospitalization events. Highlights: Patients with CTD-ILD who underwent at least one hospitalization after the initial consult had a significant decrease in transplant-free survival. When stratified by cardiopulmonary hospitalization, our study population demonstrated an over 11-fold increased risk of death. When stratified by CTD-subtype, rheumatoid arthritis was associated with reduced survival compared to other subtypes. CTD-ILD patients who were hospitalized for 7 days or greater had worse outcomes compared to those hospitalizations less than 7 days.